Flap endonuclease‐1 rs174538 G>A polymorphisms are associated with the risk of esophageal cancer in a Chinese population. Issue 3 (20th March 2017) - Sang, Yonghua; Bo, Lin; Gu, Haiyong; Yang, Wengtao; Chen, Yongbing
Abstract : Background: Esophageal cancer has a high mortality rate, particularly in Asia, and there are obvious racial differences in regard to incidence. The purpose of our study was to assess the genetic susceptibility of functional single nucleotide polymorphisms in flap endonuclease‐1 (FEN1) in esophageal squamous cell carcinoma ESCC. Methods: Clinical blood samples of 629 ESCC cases and 686 control samples were collected. The ligation detection reaction method was used to determine FEN 1 rs174538 G>A genotypes. Results: A significantly decreased risk of ESCC was associated with FEN 1 rs174538 GA genotypes among patients under 63 years old. Conclusions: Our results suggest that functional polymorphism FEN 1 rs174538 G>A might affect personal susceptibility to ESCC. This result provides a solid theoretical foundation for further clinical study using larger sample sizes.